Transcription and replication of the influenza a virus genome. - Mikulásová, A; Varecková, E; Fodor, E (2000)
The genome of influenza A virus consists of eight segments of negative-strand viral RNA (vRNA). During the replication cycle of the virus, the genomic vRNA is transcribed into positive-strand mRNA and complementary RNA (cRNA) in the cell nucleus. The promoter for the synthesis of mRNA molecules is located in a partially double-stranded RNA structure formed by the 5'- and 3'-terminal sequences of genomic vRNA segments. The virus encoded RNA-dependent RNA polymerase complex has to interact with both ends of the vRNA in order to generate capped RNA primers by endonucleolytic cleavage of cellular pre-mRNAs for the initiation of viral mRNA synthesis. Conserved sequence elements in the 5'-end, e.g. a polymerase binding site and a U(5-7) sequence are required for polyadenylation of virus-specific mRNAs. Polyadenylation occurs by reiterative copying of the U(5-7) sequence by the viral RNA polymerase, which is bound to the 5'end of the vRNA template. The U(5-7) sequence acts directly as a template for the poly(A)-tail. During the replication cycle of the virus, a "switch" from mRNA to cRNA synthesis occurs, but the mechanism by which this switch occurs remains unclear. The viral nucleoprotein and its interaction with the polymerase proteins and vRNA might play a role in this process. In contrast to transcription, the process of replication--the synthesis of cRNA and vRNA, which are known to occur in the absence of primers--is poorly understood.